Effect of foreign direct investment on economic growth and poverty in Nigeria - Haruna, Muhammad Aminu (2018)
The increasing concern by the government to reduce poverty and achieve a sustainable economic growth in Nigeria is of great importance. The objectives of this study are to examine the effect of FDI on economic growth, to assess how FDI affects poverty, and to investigate the direction of causal relationship amongst FDI, economic growth, and poverty in Nigeria. The study used time series data for the period of 1980-2015. The data were mainly sourced from the World Development Indicators (WDI), the Central Bank of Nigeria (CBN) and the National Bureau of Statistics (NBS). The study employed the approach of Autoregressive Distributive Lag (ARDL) and Granger Causality relationship in analyzing the data. The results show that FDI has a significant positive effect on economic growth in the short run and long run. However, FDI is only found to have a significant positive effect on poverty in the long run. The results of analysis also show that the models of economic growth and poverty have high speed of adjustment toward equilibrium in the short run because of high coefficient value of error correction terms. As the Granger causality relationship results confirm that FDI has unidirectional causality relationship with poverty and economic growth, the government expenditure, economic growth and trade openness are found to have bidirectional causality relationships with poverty. Therefore, this study recommends that the government of Nigeria should implement subsidies and tax relief programs to attract more FDI inflow and establish poverty alleviation commission aimed at executing specific poverty alleviation programmes.